A mind for numbers : how to excel at math and science (even if you flunked algebra) - Oakley, Barbara A., 1955- (TarcherPerigree, an imprint of Penguin Random House, 2014)
Engineering professor Barbara Oakley knows firsthand how it feels to struggle with math. She flunked her way through high school math and science courses; but when she saw how her lack of mathematical and technical savvy were limiting her options post-graduation, she returned to college newly determined to retool her brain to master the subjects that had given her so much trouble. In A mind for numbers, Oakley draws on insights from neuroscience and cognitive psychology to reveal the secrets to effectively learning math and science.